Vehicle queue detection based on morphological edge - Zhe Liu; Yangzhou Chen; Zhenlong Li (2008 7th World Congress on Intelligent Control and Automation, 2008)
In an Intelligent Traffic Systems(ITS), queue parameters at the intersections are required in many applications, such as accident monitoring and the controlling of traffic light. In this paper we use morphological edge detection to deal with the traffic image and propose a flexible window method to detect the length of the queue, which adapts to the characteristic and requirement of queue detection. The method is better than background differentiation and frame differentiation in vehicle detection and queue detection. Experimental results show that method is accurate and can run in real-time under different weather, illumination and occlusions.